2015
DOI: 10.1111/bcp.12268
|View full text |Cite
|
Sign up to set email alerts
|

Formulations for children: problems and solutions

Abstract: Paediatric formulation design is complex as there is a need to understand the developmental physiological changes that occur during childhood and their impact on the absorption of drugs. Paediatric dose adjustments are usually based on achieving pharmacokinetic or pharmacodynamic profiles equivalent to those achieved in adult populations. However, differences in the way in which children handle adult products or the use of bespoke paediatric formulations can result in unexpected pharmacokinetic drug profiles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 103 publications
1
123
0
2
Order By: Relevance
“…The eye of a newborn is approximately two-thirds of its adult size and does not reach adult size until around the age of 3 years or 4 years 21. The membranes in the eyes of newborns and infants are thin; so drug absorption and corneal permeation may be more rapid in these groups.…”
Section: Introductionmentioning
confidence: 99%
“…The eye of a newborn is approximately two-thirds of its adult size and does not reach adult size until around the age of 3 years or 4 years 21. The membranes in the eyes of newborns and infants are thin; so drug absorption and corneal permeation may be more rapid in these groups.…”
Section: Introductionmentioning
confidence: 99%
“…The sample was analyzed using HPLC at different time interval (14,28,56, and 90 days). Results revealed that the drug showed up to 90% stability at 90 th day in both the preparations and there were significant physical or chemical changes were observed neither any microbial growth was detected [8].…”
Section: Rufinamide Oral Suspensionmentioning
confidence: 96%
“…Moving to solid oral paediatric formulations (flexible solid oral dosage forms) appears to be the most sensible solution to address the above problems. Such alternative flexible solid oral dosage forms include multiparticulate formulations (minitablets, sprinkles and granules), orodispersible formulations (orodispersible minitablets, disintegrating tablets, oral strips, buccal wafers, medicated lollipops) and dispersible tablets [40,41,42,43].…”
Section: Recent Paradigm Shift In Paediatric Oral Formulationsmentioning
confidence: 99%